Degree of Microbial Contaminants Isolated from Smart Mobile Phones Used by University Students in Bangladesh (Bangladesh Journal of Infectious Diseases, 2025)
Background: Microbial survival capabilities on smartphone surfaces works as a major source of harmful microbial transmission among users.Objectives: This study sought to determine the microbial growth on the surface of smartphones, used by students of Jahangirnagar University in Bangladesh.Methodology: This cross-sectional study, from May to August 2021, involved 20 students, where 8 (40%) were females and 12 (60%) were males. The socio-demographic data and information about their phone usage  were collected utilizing a self-administered questionnaire. A sterile swab was rotated over the surface of both sides of each smartphone, and moistened with sterile saline. All swabs were cultured on MacConkey Agar and Nutrient Agar and examined for growth. Plates were incubated aerobically at 370C for 48h and identification was done as per standard laboratory procedures.Results: Out of the total 20 swab samples collected, 16 (80%) of them presented with bacterial growth, and 10 (50%) of them presented with fungal growth. Gram-positive bacteria occurred on smartphones at 89.7%, whereas Gram-negative bacteria were contaminated at 10.03%. The total frequency of one or several micro-organisms on smartphones was 100%. The predominant isolates were Staphylococcus epidermidis (37.1%) and Staphylococcus aureus (37.1%). Other isolates were Klebsiella sp. (5.7%) and Escherichia coli (2.9%). No significant association was found between smartphone contamination and gender, age group, educational level, phone sharing, presence of scratches, use of front cover, and regular cleaning of smartphones.Conclusion: The study indicated that smartphones used by students are a vehicle for several microorganisms. According to the findings of this study, smartphones have the potential to act as a mode of transportation for various micro-organisms.Bangladesh Journal of Infectious Diseases, December 2024;11(2):108-114